2015
DOI: 10.1253/circj.cj-15-0982
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of 3-Dimensional Echocardiography in the USA

Abstract: Three-dimensional (3D) echocardiography is one of the most promising methods for the diagnosis of cardiac disease. Left and right ventricular size and function are currently evaluated with 2D echocardiography. However, for unpredictable asymmetry of the chamber geometry, conventional 2D echocardiography cannot be used to accurately determine absolute chamber volumes and ejection fraction. As for valvular heart diseases, the 3D echo approach has proven to be the most unique, powerful, and convincing method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 176 publications
0
4
0
Order By: Relevance
“…The utility of 3D transesophageal echocardiography (TEE) for evaluating the detailed pathogenesis of MR has been widely accepted. 14, 15 Accordingly, the present study aimed to investigate the characteristics of the MV structure and dynamics through 3D-TEE in patients with atrial functional MR and lone persistent AF.…”
mentioning
confidence: 99%
“…The utility of 3D transesophageal echocardiography (TEE) for evaluating the detailed pathogenesis of MR has been widely accepted. 14, 15 Accordingly, the present study aimed to investigate the characteristics of the MV structure and dynamics through 3D-TEE in patients with atrial functional MR and lone persistent AF.…”
mentioning
confidence: 99%
“…Notably, 3D TEE is an excellent procedure for patients with ASDs of complex anatomies, such as multiple defects, because it provides a high spatial resolution of all defects, implanted devices, and any residual shunting [11,[23][24][25][26][27][28]. Several studies have demonstrated that 3D TEE adequately visualizes the interatrial septum of complex ASDs during transcatheter ASD closure [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive literature reporting the value of 3D echocardiography in specific congenital cardiac defects. It has proven most helpful for the evaluation of the mitral valve where it provides physiologic, morphologic and functional assessment [ 9 ]. Three-dimensional echocardiography is a more sensitive modality compared with 2D in identifying the lesion in the mitral valve apparatus responsible for pathology [ 10 ].…”
Section: Three-dimensional Echocardiographymentioning
confidence: 99%